A comparison of the analytical level of agreement of nine treponemal assays for syphilis and possible implications for screening algorithms. Issue 9 (19th September 2013) - Castro, Arnold; Jost, Heather; Cox, David; Fakile, Yetunde; Kikkert, Susan; Tun, Ye; Zaidi, Akbar; Park, Mahin
Abstract : Objective: The serological diagnosis of syphilis requires the detection of two distinct antibodies, the non-treponemal and trepomenal. Center for Disease Control and Prevention (CDC) recommends screening first with a non-treponemal test such as (Rapid Plasma Reagin/Venereal Disease Research Laboratory), and then confirming those results with one of the several treponemal tests (Fluorescent Treponemal Antibody-Absorption (FTA-ABS), Enzyme Immunoassay, chemiluminescence, treponema pallidum particle agglutination (TP-PA) or Point of Care). Owing to the high volume of samples processed by some laboratories using automated systems, the screening with treponemal assays and confirming with non-treponemal tests is becoming the established norm. The purpose of this study was to evaluate eight treponemal assays using TP-PA as the predicate assay. Methods: 290 stored serum samples were tested qualitatively according to the manufacturer's directions. Results: Concordance with specimens tested as reactive or non-reactive using TP-PA was: FTA-ABS 94.5–100%, Trep-Sure 100–98.9%, BioELISA 100–98.9%, INNO-LIA 99.1–99.4%, BIOLINE 100–98.9%, CAPTIA IgG 100–97.2%, Trep-ID 100–100% and LIAISON 100–99.4%. In order to properly evaluate the performance of these assays, the analytical sensitivity was determined by endpoint titration of serial dilutions of the reactive serum samples in normal sera. The median endpoint titre varied from 1:4 for FTA-ABS to 1:512 for Trep-Sure. Conclusions: The performance of the treponemal serological assays was comparable while using medium and high-titre sera. However, the varying performance on specimen dilutions suggests that there may be differences in sensitivity with low-titre sera that are more prevalent in primary and late syphilis cases.